ISABEL: a web-based differential diagnostic aid for paediatrics: results from an initial performance evaluation. Issue 5 (1st May 2003) - Ramnarayan, P; Tomlinson, A; Rao, A; Coren, M; Winrow, A; Britto, J
Abstract : Aims: To test the clinical accuracy of a web based differential diagnostic tool (ISABEL) for a set of case histories collected during a two stage evaluation. Methods: Setting: acute paediatric units in two teaching and two district general hospitals in the southeast of England. Materials: sets of summary clinical features from both stages, and the diagnoses expected for these features from stage I (hypothetical cases provided by participating clinicians in August 2000) and final diagnoses for cases in stage II (children presenting to participating acute paediatric units between October and December 2000). Main outcome measure: presence of the expected or final diagnosis in the ISABEL output list. Results: A total of 99 hypothetical cases from stage I and 100 real life cases from stage II were included in the study. Cases from stage II covered a range of paediatric specialties (n = 14) and final diagnoses (n = 55). ISABEL displayed the diagnosis expected by the clinician in 90/99 hypothetical cases (91%). In stage II evaluation, ISABEL displayed the final diagnosis in 83/87 real cases (95%). Conclusion: ISABEL showed acceptable clinical accuracy in producing the final diagnosis for a variety of real as well as hypothetical case scenarios.